High frequency of Lamivudine and Telbivudine resistance mutations in hepatitis B virus isolates from human immunodeficiency virus co-infected patients on highly active antiretroviral therapy in Bucaramanga, Colombia - Bautista-Amorocho, Henry; Silva-Sayago, Jorge Alexander; Picón-Villamizar, Jirehl (Frontiers in Microbiology, 2023)
Hepatitis B virus (HBV) antiviral Resistance-Associated Mutations (RAMs) in human immunodeficiency virus (HIV) coinfected patients undergoing highly active antiretroviral therapy (HAART) are complex and incompletely understood. We aim to determine the prevalence of HBV coinfections, HBV genotypes, and RAMs in a cohort of HIV-infected patients in the northeast region of Colombia. This was a cross-sectional study in HIV patients between February 2013 and February 2014. Virological, immunological and HAART were collected from clinical records. An in-house nested PCR and Sanger sequencing of HBV pol gene was used to identify coinfections, genotypes, RAMs and HBV s antigen (HBsAg) escape mutants. Out of 275 subjects, 11.6% were identified as HIV-HBV coinfections from which 3.3% were HBsAg positive (active hepatitis B) while 9.3% were occult hepatitis B infections (OBI). All HBV sequences (n=23) belonged to genotype F3. Among HIV/HBV coinfections, 71.9% had CD4+ T cell counts above 200 cells/mm3 and 37.5% undetectable HIV viral loads. RAMs rtL80I, rtL180M, and rtM204V, which confer resistance to Lamivudine/ Telbivudine and partially resistant to Entecavir, were found in all HBV isolates. Also, a rt236Y unknown mutation to Tenofovir was identified. Most patients under HAART received first-generation HBV antiviral therapy with a low genetic barrier to resistance. Antiviral Drug-associated Potential Vaccine-escape Mutations (ADAPVEMs) in S gene were observed in all isolates ranging from 1-20 amino acid substitutions. However, no vaccine escape mutants were detected. In Summary, these findings highlight the importance of molecular HBV screening, antiviral resistance monitoring and new guidelines in HIV patients to overcome RAMs and prevent HBV-related liver diseases.